Stress Prevention@Work: a study protocol for the evaluation of a multifaceted integral stress prevention strategy to prevent employee stress in a healthcare organization: a cluster controlled trial - Rianne J. A. Hoek; Bo M. Havermans; Irene L. D. Houtman; Evelien P. M. Brouwers; Yvonne F. Heerkens; Moniek C. Zijlstra-Vlasveld; Johannes R. Anema; Allard J. van der Beek; Cécile R. L. Boot (BMC, 2017)
Abstract Background Adequate implementation of work-related stress management interventions can reduce or prevent work-related stress and sick leave in organizations. We developed a multifaceted integral stress-prevention strategy for organizations from several sectors that includes a digital platform and collaborative learning network. The digital platform contains a stepwise protocol to implement work-related stress-management interventions. It includes stress screeners, interventions and intervention providers to facilitate access to and the selection of matching work-related stress-management interventions. The collaborative learning network, including stakeholders from various organizations, plans meetings focussing on an exchange of experiences and good practices among organizations for the implementation of stress prevention measures. This paper describes the design of an integral stress-prevention strategy, Stress Prevention@Work, and the protocol for the evaluation of: 1) the effects of the strategy on perceived stress and work-related outcomes, and 2) the barriers and facilitators for implementation of the strategy. Methods The effectiveness of Stress Prevention@Work will be evaluated in a cluster controlled trial, in a large healthcare organization in the Netherlands, at six and 12 months. An independent researcher will match teams on working conditions and size and allocate the teams to the intervention or control group. Teams in the intervention group will be offered Stress Prevention@Work. For each intervention team, one employee is responsible for applying the strategy within his/her team using the digital platform and visiting the collaborative learning network. Using a waiting list design, the control group will be given access to the strategy after 12 months. The primary outcome is the employees' perceived stress measured by the stress subscale of the Depression, Anxiety, and Stress Scale (DASS-21). Secondary outcome measures are job demands, job resources and the number of preventive stress measures implemented at the team level. Alongside the trial, a process evaluation, including barriers and facilitators of the implementation of Stress Prevention@Work, will be conducted in one healthcare organisation. Discussion If Stress Prevention@Work is found to be effective in one healthcare organisation, further implementation on a broader scale might lead to increased productivity and decreased stress and sick leave in other organizations. Results are expected in 2018. Trial registration NTR5527 . Registered 7 Dec 2015.